IMPLEMENTASI KURIKULUM MERDEKA DALAM PENINGKATAN LITERASI PESERTA DIDIK DI SEKOLAH DASAR - Ummie Masrurah; Fitri Puji Rahmawati; Anik Ghufron (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to describe how the implementation of the Kurikulum Merdeka (Independent Curriculum) can improve literacy in elementary schools. The research method used is qualitative research with a descriptive qualitative approach through a literature review. This study identifies and analyzes relevant literature regarding the Kurikulum Merdeka and its impact on student literacy. The results show that the Kurikulum Merdeka has a positive impact on enhancing student literacy through several key aspects: improving literacy skills (reading, writing, and critical thinking), contextual learning relevant to everyday life, the use of technology to support learning, and the development of a literacy culture in schools. However, this study also reveals some challenges in its implementation, including the readiness of teachers and schools, access to technology, and limited resources. To address these challenges, effective strategies include teacher training and development, increasing the availability of resources, developing creative literacy programs, and using diverse evaluation methods. Thus, this study concludes that the Kurikulum Merdeka has great potential to improve literacy in elementary schools, but requires proper support and strategies to optimize the results.